Root Canal Treatment Survival Analysis in National Dental PBRN Practices. (October 2022) - Thyvalikakath, T.; LaPradd, M.; Siddiqui, Z.; Duncan, W.D.; Eckert, G.; Medam, J.K.; Rindal, D.B.; Jurkovich, M.; Gilbert, G.H.; ,
Few studies have examined the longevity of endodontically treated teeth in nonacademic clinical settings where most of the population receives its care. This study aimed to quantify the longevity of teeth treated endodontically in general dentistry practices and test the hypothesis that longevity significantly differed by the patient's age, gender, dental insurance, geographic region, and placement of a crown and/or other restoration soon after root canal treatment (RCT). This retrospective study used deidentified data of patients who underwent RCT of permanent teeth through October 2015 in 99 general dentistry practices in the National Dental Practice-Based Research Network (Network). The data set included 46, 702 patients and 71, 283 RCT permanent teeth. The Kaplan–Meier (product limit) estimator was performed to estimate survival rate after the first RCT performed on a specific tooth. The Cox proportional hazards model was done to account for patient- and tooth-specific covariates. The overall median survival time was 11.1 y; 26% of RCT teeth survived beyond 20 y. Tooth type, presence of dental insurance any time during dental care, placement of crown and/or receiving a filling soon after RCT, and Network region were significant predictors of survival time ( P < 0.0001). Gender and age were not statistically significant predictors in univariable analysis, but in multivariable analyses, gender was significant after accounting for other variables. This study of Network practices geographically distributed across the United States observed shorter longevity of endodontically treated permanent teeth than in previous community-based studies. Also, having a crown placed following an RCT was associated with 5.3 y longer median survival time. Teeth that received a filling soon after the RCT before the crown was placed had a median survival time of 20.1 y compared to RCT teeth with only a crown (11.4 y), only a filling (11.2 y), or no filling and no crown (6.5 y).